2019
DOI: 10.1111/cdep.12330
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Ethnotheories of Maladaptive Behavior in Young Children

Abstract: Parents' culturally influenced belief systems, or ethnotheories, are critical components of children's socialization. Beliefs about children's desirable characteristics motivate specific parenting activities and moderate the effectiveness of childrearing practices. However, relatively little attention has been given to parents' ethnotheories of children's undesirable behavior. From a few studies, we know that parents have culturally specific theories about the nature and management of children's maladaptive be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…Some scholars proposed that mothers with lower education were more likely to indulge, oppress, punish, and Occupational Therapy International neglect children than mothers with higher education who advocate democratic upbringing [20]. Other researchers believed that older parents treated their children in a relatively effective way, while younger parents treated their children in a simple and rough manner [21].…”
Section: Attribute Theorymentioning
confidence: 99%
“…Some scholars proposed that mothers with lower education were more likely to indulge, oppress, punish, and Occupational Therapy International neglect children than mothers with higher education who advocate democratic upbringing [20]. Other researchers believed that older parents treated their children in a relatively effective way, while younger parents treated their children in a simple and rough manner [21].…”
Section: Attribute Theorymentioning
confidence: 99%
“…Although risk factors like poverty and maternal depression appear to be similar across settings, individuals' experiences of risks, their impact on parenting practices, and the meaning and function of these practices may vary in a culturally dependent fashion (Bornstein, 2010). Culture and cultural scripts offer a variety of definitions about accepted and nonaccepted behavior in children, contributing to specific ethnotheories or belief systems about children's behavior that ultimately guide parental socialization efforts (Olson, Lansford, Evans, Blumstein, & Ip, 2019). Cross-cultural studies of parenting and EP have consistently found significant within-and between-culture variance (Deater-Deckard et al, 2018), such that, for example, higher EP was predicted by within-culture (or individuallevel) differences in parental authoritarian attitudes and endorsement of aggression, and further augmented by differences in endorsement of aggression between-cultures (Lansford et al, 2018).…”
Section: Risk Factors In National Context: the Case Of Chilementioning
confidence: 99%
“…Although the study of cultural commonalities in parent-child relationships has a long history [12], only recently scholars have examined how parents' cultural belief and perceptions systems explain the nature and quality of parenting and family interactions in particular social contexts [13,14]. Given the implicit nature of parents' perceptions about their parent-child relationships in a particular cultural context [15], cross-national research entails methodological and theoretical difficulties when assessing parents' perceptions using quantifiable measures across and within cultures [4]. Using a translated version of the Child-parent Relationship Scale (CPRS), which was originally developed based on a Western sample, this study adds to the current discussion on the cultural relevance and reliability of measures used to examine parental perceptions about parent-child relationships across socio-cultural contexts.…”
Section: Introductionmentioning
confidence: 99%